TECHNIQUES OF IMPROVING THE ADMINISTRATIVE-LEGAL MEANS OF ELECTORS' RIGHTS PROTECTION - A. Nasybullin (Russian Journal of Economics and Law)
The author attempts to critically approach the modern system of Administrative-legal means of electors' rights protection, analyzes the process of -pre-court protection of election rights, views the drawbacks of the functioning Federal Law On the main guarantees of election rights and referendum rights of the Russia Federation citizens and suggests innovations in normative acts.